Towards Innovative Science Learning: Needs Analysis for Developing Interactive Hypermedia to Foster Creative Thinking and Science Process Skills of Prospective Elementary School Teachers - Nurkamilah, Siti; Sopandi, Wahyu; Darmawan, Deni (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to analyze the dynamics of students’ needs for the development of interactive hypermedia in science learning to foster creative thinking skills and science process skills among prospective elementary school teachers. This study employed a quantitative descriptive approach using a questionnaire as the primary instrument. The participants consisted of 241 students from 13 Primary School Teacher Education programs across Indonesia. Data were collected through an online survey and analyzed using an interactive analysis model involving data collection, data reduction, data display, and conclusion drawing. The findings reveal a very high level of need for the development of interactive hypermedia in science courses. Most respondents indicated that interactive hypermedia should integrate project-based learning tasks, brainstorming activities, inquiry training components, gamification elements, contextual materials aligned with the elementary school curriculum, and science literacy development. The results also indicate that although students strongly believe that interactive hypermedia can enhance creativity, communication skills, motivation, and engagement, its actual implementation in science lectures remains very limited. The novelty of this study lies in providing comprehensive empirical evidence regarding the specific design requirements of interactive hypermedia that systematically integrates creative thinking, science process skills, self-regulated learning, gamification, and contextual science literacy within a unified instructional framework for science education.